Efficacy of underground aggregate infiltration beds under a permeable pavement system - Liv Haselbach; Mitchell Fountain; Golnoosh Toosi; Hossein Hariri Asli (Discover Water)
Abstract Pervious concrete (PC) pavement systems with their underlying aggregate storage beds provide potential strategies to mitigate stormwater runoff and associated flooding issues. Of particular interest is the efficacy of the infiltration capabilities into the soil of the underground storage bed, especially in areas with slow draining soils. This study uses real-time data on the water levels in the storage beds to determine soil infiltration rates at two test sites in Southeast Texas. One of the sites is connected to a rain garden system, with the potential for taking advantage of the low impact development (LID) processes of both systems. It was found that the combined systems allowed water to flow between them possibly adding additional storage during a storm event with the PC system’s void spaces and allowing for additional evaporative processes from the rain garden post the event. The other site has the PC raised above the surrounding grade, which represents potential applications where structures are raised above base flood elevations with connecting paved areas also raised. It was found that this raised system provided both infiltration into the soils from the underground bed and some detention capabilities in the raised portion of the system. These results aid in designing these LID systems in flat areas subject to flooding with slow draining soils such as in much of the coastal Gulf region.